2011
DOI: 10.1007/978-3-7091-0693-8_53
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Hemorrhage and Meteorological Factors in Chongqing, in the Southwest of China

Abstract: Studies have reported the relationship between intracerebral hemorrhage (ICH) and meteorological factors. However, few of those study analyses were dependent on daily meteorological factors. The aim of this study is to evaluate the relationship between various meteorological data and ICH cases from Chongqing, in the southwest of China. One thousand nineteen intracerebral hemorrhage events registered in our hospital were recorded from 1 January 2006 to 30 August 2009. Meteorological parameters were analyzed, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Other major causes of ICH were thrombopenia, leukemia, and cerebrovascular malformations, especially in patients <30 years of age. Li et al (2011) reported that the incidence of ICH throughout the year was closely related to meteorological factors such as season, daily air temperature, humidity, and atmospheric pressure. We found that the incidence of ICH was highest in winter and lowest in summer, consistent with their results, although the differences did not reach statistical significance in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Other major causes of ICH were thrombopenia, leukemia, and cerebrovascular malformations, especially in patients <30 years of age. Li et al (2011) reported that the incidence of ICH throughout the year was closely related to meteorological factors such as season, daily air temperature, humidity, and atmospheric pressure. We found that the incidence of ICH was highest in winter and lowest in summer, consistent with their results, although the differences did not reach statistical significance in our study.…”
Section: Discussionmentioning
confidence: 99%
“…TEM is a noticed meteorological parameter affecting ICH occurrence. Most studies from different climate types show that TEM negatively correlates with ICH risk, 8 , 9 , 14 , 16 , 21–25 although a few studies suggest that TEM is not a risk factor. 11–13 In the present research, we found daily mean TEM and day-to-day variation of TEM influenced the risk of ICH meaningfully in the single-factor model.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Many researchers indicate that changes in meteorological parameters, including temperature (TEM), atmospheric pressure (PRE), and relative humidity (RHU), are significantly related to the risk of ICH. [8][9][10] However, some scholars have opposite opinions on these views. [11][12][13] Moreover, the influence type of meteorological parameters on ICH occurrence is controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Odds ratios for the association of SAH risk and an interquartile range 24 h change in ambient temperature of 2.9 °C, relative air humidity of 10.5% and atmospheric pressure of 6.2 hPa for lag times of 1, 2, and 3 days before onset of SAH symptoms in the overall population and subgroups. Bars indicate 95% confidence interval, filled squares mark odds ratios with confidence intervals not including 1.00 different geographical regions [28,[37][38][39][40][41][42][43][44][45]. However, others found an increased SAH risk associated with falling atmospheric pressure [46] or no such association [32,47,48] or no association with SAH risk and weather fronts [49].…”
Section: Discussionmentioning
confidence: 99%